1996
DOI: 10.1143/jjap.35.l1072
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Growth of Diamond on Iridium

Abstract: Epitaxial growth of diamond on iridium thin films was performed by direct-current plasma chemical vapor deposition with ion irradiation pretreatment of the substrate. Pyramidal epitaxial diamond particles with a number density of ∼108 cm-2 were grown on the iridium film. The epitaxial relation is written as (100) diamond//(100) iridium and [001] diamond//[001] iridium. Tilting of the epitaxial relation, as occasionally observed for diamond on silicon or beta silicon carbide, is scarcely observed. Erosion,as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(51 citation statements)
references
References 4 publications
0
51
0
Order By: Relevance
“…The latter is available since the bias enhanced nucleation (BEN) process has been introduced [5]. With iridium Ohtsuka et al [6] found a material which provides an ideal substrate for heteroepitaxial diamond deposition ten years ago.…”
Section: Introductionmentioning
confidence: 99%
“…The latter is available since the bias enhanced nucleation (BEN) process has been introduced [5]. With iridium Ohtsuka et al [6] found a material which provides an ideal substrate for heteroepitaxial diamond deposition ten years ago.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the Ir substrate surface after the ion irradiation is somewhat rough, and amorphous carbon is deposited by RHEED and X-ray spectroscopy (XPS) [25]. Furthermore, with a growth time of 30 minutes for the diamond, a flat continuous film as shown in Fig.…”
Section: Epitaxial Growth On An Ir Surfacementioning
confidence: 97%
“…Although bulk Ir is a material with poor machinability, it can be epitaxially grown easily on a single-crystal substrate surface, such as MgO and SrTiO 3 . With the above background, the authors attempted growth of diamond on Ir{100) epitaxial thin film surfaces [25,44,53]. The details are given below.…”
Section: Epitaxial Growth On An Ir Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…This aspect of diamond has attracted considerable research interest in the last decades and a variety of substrates have been used for the textured growth of diamond films by CVD methods in the last decades. Promising substrates for oriented/epitaxial growth of diamond are iridium, nickel, cobalt, silicon and platinum [1][2][3][4][5]. GaN is another promising candidate, for use in power FETs, blue lasers and light emitting diodes.…”
Section: Introductionmentioning
confidence: 99%